Environment-friendly microemulsion cutting fluid and production process thereof

By using environmentally friendly ingredients such as nanoborate and modified organic borate in the cutting fluid, the limitations of traditional cutting fluids in lubrication and rust prevention performance are solved, and more efficient metal processing and lower environmental pollution are achieved. .

CN119505986AInactive Publication Date: 2025-02-25JIANGSU SUYU ELECTRONIC MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411693438.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional cutting fluids have limitations in lubrication and rust prevention properties, and contain substances that are harmful to the environment and human health, resulting in pollution and health risks.

Method used

Develop an environmentally friendly microemulsified cutting fluid to enhance lubrication and rust resistance through ingredients such as nanoborate and modified organic borate, form a protective film, reduce friction coefficient, and pass environmentally friendly defoaming agents and surfactants. Achieve emulsification effect.

Benefits of technology

It significantly improves the wear resistance of tools and workpieces, extends service life, improves processing accuracy and surface quality, and meets environmental protection requirements and reduces pollution and maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses environment-friendly microemulsion cutting fluid and a production process thereof, and relates to the technical field of cutting fluid. Comprising 10 to 15 parts by mass of base oil, 1 to 3 parts by mass of zinc dialkyl dithiophosphate, 0.3 to 0.6 part by mass of benzotriazole, 0.3 to 0.6 part by mass of an environment-friendly defoaming agent, 7 to 9 parts by mass of organic alcohol amine, 9 to 12 parts by mass of a novel nonionic surfactant, 1 to 1.5 parts by mass of an environment-friendly anionic surfactant, 6 to 8 parts by mass of high-performance polyether and 4 to 6 parts by mass of span. The invention discloses a water-based paint which is prepared from the following components in parts by mass: 14-16 parts of deionized water, 0.15-0.3 part of nano borate and 0.6-1.2 parts of modified organic boric acid ester. According to the environment-friendly micro-emulsion cutting fluid and the production process thereof, the lubricating effect is further enhanced by adding the nano borate, a layer of protective film can be formed on the metal surface, the wear resistance of a tool and a workpiece is improved, the friction coefficient is reduced, the service life of the tool is prolonged, and the machining precision and the surface quality are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cutting fluids, in particular to an environmentally friendly micro-emulsified cutting fluid and a production process thereof. Background Art

[0002] In the field of metal processing, cutting fluid plays a vital role.

[0003] On the one hand, many traditional cutting fluids contain a large amount of substances that are harmful to the environment, such as heavy metals, some difficult-to-degrade organic compounds, and chemical additives that pose a potential threat to human health. These substances will cause serious pollution to the soil, water and atmospheric environment during the use, discharge and subsequent treatment of cutting fluids, which is inconsistent with modern environmental protection concepts and increasingly stringent environmental protection regulations.

[0004] On the other hand, traditional cutting fluids have limitations in terms of lubrication and anti-rust performance. In terms of lubrication performance, they cannot provide sufficiently excellent lubrication for tools and workpieces, resulting in increased wear of tools during the cutting process and shortened service life.

[0005] Therefore, there is an urgent need to develop a new type of cutting fluid that can not only meet environmental protection requirements but also have significantly improved lubrication and anti-rust properties, so as to solve the above-mentioned problems existing in existing cutting fluids and improve the overall efficiency and sustainability of metal processing. Summary of the invention

[0006] To achieve the above objectives, the present invention is implemented through the following technical scheme: an environmentally friendly micro-emulsified cutting fluid, composed of the following raw materials in parts by weight: 10-15 parts by mass of base oil, 1-3 parts by mass of zinc dialkyl dithiophosphate, 0.3-0.6 parts by mass of benzotriazole, 0.3-0.6 parts by mass of environmentally friendly defoaming agent, 7-9 parts by mass of organic alcohol amine, 9-12 parts by mass of new non-ionic surfactant, 1-1.5 parts by mass of environmentally friendly anionic surfactant, 6-8 parts by mass of high-performance polyether, 4-6 parts by mass of Span, 14-16 parts by mass of deionized water, 0.15-0.3 parts by mass of nano borate and 0.6-1.2 parts by mass of modified organic borate.

[0007] The addition of nano-borates further enhances the lubrication effect. It can form a protective film on the metal surface, improve the wear resistance of tools and workpieces, reduce the friction coefficient, extend the service life of tools, and improve processing accuracy and surface quality.

[0008] Preferably, it is composed of the following raw materials in parts by weight: 12.5 parts by mass of base oil, 2 parts by mass of zinc dialkyl dithiophosphate, 0.36 parts by mass of benzotriazole, 0.5 parts by mass of environmentally friendly defoaming agent, 8 parts by mass of organic alcohol amine, 10 parts by mass of new non-ionic surfactant, 1.2 parts by mass of environmentally friendly anionic surfactant, 7 parts by mass of high-performance polyether, 5 parts by mass of Span, 15 parts by mass of deionized water, 0.25 parts by mass of nano borate and 1 part by mass of modified organic borate.

[0009] Preferably, the environmentally friendly defoaming agent is a natural oil defoaming agent, the organic alcohol amine is ethanolamine, the new non-ionic surfactant is a block polyether, the environmentally friendly anionic surfactant is sodium lignin sulfonate, the high-performance polyether is polyethylene glycol ether, and the nano borate is nano calcium borate.

[0010] Preferably, the preparation method of the modified organic borate is specifically as follows: Step A1, first modification; Prepare boric acid, polyol and catalyst, weigh the raw materials boric acid and polyol; Add boric acid and polyol into a reaction kettle equipped with a stirring device, a thermometer and a reflux condenser, add a catalyst, slowly heat up to 120-150°C, and keep stirring at this temperature for 3-5 hours; detect the acid value of the reaction system during the reaction, and stop the reaction when the acid value reaches a predetermined value; The predetermined value is an acid value less than 10 mgKOH / g; The reaction product is subjected to reduced pressure distillation to remove unreacted polyol and generated water to obtain a preliminarily modified boric acid ester; Step A2, second modification; Take the borate product obtained by the first modification, and prepare an organic amine with anti-rust function and an initiator; Add the borate product and organic amine to the reactor and stir evenly. Pass nitrogen to protect and remove oxygen from the system. Heat to 80-100°C and add initiator. Keep the temperature to react for 4-6 hours. After the reaction is completed, cool to room temperature; Step A3, third modification; Taking the second modified product, preparing a long-chain fatty acid and a catalyst having steric hindrance effect and environmental protection characteristics; Add the second modified product and long-chain fatty acid into the reactor. Add the catalyst and stir evenly. Heat to 100-120°C and react for 3-5 hours to obtain the third modified organic borate. Step A4, modification and adjustment; Take the three modified organic borate products, prepare glycerophosphate and potassium carbonate, the amount of potassium carbonate is 2%-5% of the mass of glycerophosphate; The final modified organic borate and glycerophosphate are added to a reaction kettle equipped with a stirring device, a thermometer and a reflux condenser in a certain molar ratio of 1:0.5-0.8, and potassium carbonate is added. Under a nitrogen atmosphere, the temperature is slowly raised to 60-80°C, and the reaction is maintained at this temperature for 5-8 hours with stirring to obtain the final product, the modified organic borate.

[0011] The anti-rust function of glycerol phosphate is introduced into the organic borate system, thereby further enhancing its anti-rust performance; at the same time, the reaction conditions are relatively mild, which can reduce the damage to the original organic borate structure to a certain extent.

[0012] After multiple modifications, the modified organic borate has good anti-rust properties. Its molecular structure can be tightly adsorbed on the metal surface to form a dense anti-rust film, which can effectively resist the erosion of moisture, oxygen and other corrosive media and extend the anti-rust period of workpieces and machine tools.

[0013] Preferably, in step A1, the molar ratio of the weighed raw material boric acid:polyol is 1:1.2-1.5, the polyol is specifically ethylene glycol, the catalyst is specifically toluenesulfonic acid, and the dosage of the added catalyst is 0.5-1% of the total mass of the reactants; In step A2, the molar ratio of borate ester to organic amine is 1:1-1.2, the amount of initiator used is 1%-3% of the mass of the organic amine, the organic amine is specifically diethanolamine, and the initiator is specifically dibenzoyl peroxide; In the step A3, the molar ratio of the second modified product to the long-chain fatty acid is 1:0.8-1, the amount of the catalyst is 0.5%-1% of the mass of the long-chain fatty acid, the long-chain fatty acid is specifically stearic acid, and the catalyst is specifically tetrabutyl titanate.

[0014] A production process of an environmentally friendly micro-emulsified cutting fluid comprises the following steps: Step B1, premixing; Add the base oil into the reactor and start the stirring device; add zinc dialkyl dithiophosphate, benzotriazole, organic alcohol amine and Span in sequence during the stirring process, and stir for 15-20 minutes to obtain a preliminary reagent A, so that these components are fully dissolved and evenly mixed in the base oil; Step B2, surfactant mixing; Add new nonionic surfactant, environmentally friendly anionic surfactant and high-performance polyether to the preliminary reagent A, increase the stirring speed to 600-800r / min, and stir for 20-30 minutes to obtain the preliminary emulsified reagent B, so that the surfactant is fully mixed and interacts with the base oil and other ingredients to form a preliminary emulsified system. Step B3, nano borate dispersion treatment; Add nanoborate to deionized water and use an ultrasonic disperser to disperse the nanoborate for 20-30 minutes to evenly disperse the nanoborate in the water to form a nano suspension; Add the dispersed nanoborate suspension and preliminary emulsifying agent B into the reactor and stir to obtain emulsion C; ensure that the nanoborate is evenly dispersed in the entire system. Step B4, adding water for emulsification; Slowly add deionized water to the reactor, control the water addition speed through the flow meter, control the water addition speed at 1-2L per minute, maintain the stirring speed at 800-1000r / min, and reduce the temperature of the reactor to 30-40℃; With the addition of water, the system gradually changes from an oil-in-water emulsion to an oil-in-water emulsion. Observe the state of the emulsion. When the emulsion becomes uniform, delicate and has no obvious oil droplets, it means that the emulsification is basically completed.

[0015] Step B5, adding modified organic borate and defoamer; Add the modified organic borate to the emulsion, reduce the stirring speed to 300-500r / min, and stir for 10-15 minutes to evenly disperse the modified organic borate in the cutting fluid to give full play to its anti-rust performance. Add an environmentally friendly defoamer and continue stirring for 5-10 minutes to finally obtain an environmentally friendly micro-emulsified cutting fluid.

[0016] Ingredients such as zinc dialkyl dithiophosphate also have certain anti-rust and anti-wear properties. They work synergistically with other rust inhibitors to further improve the anti-rust effect of the cutting fluid, meet the anti-rust requirements in the metal processing process, and reduce the equipment maintenance and replacement costs caused by rust.

[0017] Preferably, the stirring speed of the stirring device in step B1 is controlled at 300-500 r / min, and the temperature is slowly raised to 40-50° C.

[0018] Preferably, in step B3, the stirring speed of the reactor is 600-800 r / min, and the stirring time is 15-20 minutes.

[0019] The present invention provides an environmentally friendly micro-emulsified cutting fluid and a production process thereof. It has the following beneficial effects: 1. The environmentally friendly micro-emulsified cutting fluid and its production process further enhance the lubrication effect by adding nano-borates, which can form a protective film on the metal surface, improve the wear resistance of the tool and workpiece, reduce the friction coefficient, extend the tool life, and improve processing accuracy and surface quality.

[0020] 2. The environmentally friendly micro-emulsified cutting fluid and its production process have good anti-rust properties through multiple modifications of modified organic borate esters. Its molecular structure can be tightly adsorbed on the metal surface to form a dense anti-rust film, which can effectively resist the erosion of moisture, oxygen and other corrosive media, and extend the anti-rust period of workpieces and machine tools.

[0021] 3. The environmentally friendly micro-emulsified cutting fluid and its production process also have certain anti-rust and anti-wear properties through ingredients such as dialkyl dithiophosphate zinc. The synergistic effect with other rust inhibitors further improves the anti-rust effect of the cutting fluid, meets the anti-rust requirements in the metal processing process, and reduces the equipment maintenance and replacement costs caused by rust.

[0022] Fourth, the environmentally friendly microemulsified cutting fluid and its production process use organic borate esters that have been modified three times in its formula. First, boric acid is reacted with polyols through esterification reaction to introduce polyol structure, which improves its solubility and compatibility with other ingredients. Then, a grafting reaction is carried out to graft organic amines with anti-rust function onto borate molecules to enhance their anti-rust performance. Finally, the molecular structure is optimized and long-chain fatty acids are added to give it a steric hindrance effect, which improves the stability and durability of the modified organic borate ester and can form a more durable anti-rust film on the metal surface.

[0023] 5. The environmentally friendly micro-emulsified cutting fluid and its production process, wherein the thrice-modified organic borate ester is subjected to a composite reaction with glycerol phosphate. This composite modification enables the modified organic borate ester to have more functional groups, which can better combine with the metal surface, enhance the anti-rust effect, and may also have a certain synergistic lubrication and anti-wear effect. DETAILED DESCRIPTION

[0024] The present invention will be further described in detail below in conjunction with specific embodiments. The embodiments of the present invention are provided for the purpose of illustration and description, and are not intended to be exhaustive or to limit the present invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described to better illustrate the principles and practical applications of the present invention, and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.

[0025] In the first embodiment, the present invention provides a technical solution: An environmentally friendly micro-emulsified cutting fluid is composed of the following raw materials in parts by weight: 10 parts by mass of base oil, 1 part by mass of zinc dialkyl dithiophosphate, 0.3 parts by mass of benzotriazole, 0.3 parts by mass of environmentally friendly defoaming agent, 7 parts by mass of organic alcohol amine, 9 parts by mass of new non-ionic surfactant, 1 part by mass of environmentally friendly anionic surfactant, 6 parts by mass of high-performance polyether, 4 parts by mass of Span, 14 parts by mass of deionized water, 0.15 parts by mass of nano borate and 0.6 parts by mass of modified organic borate.

[0026] The environmentally friendly defoaming agent is specifically a natural oil defoaming agent, the organic alcohol amine is specifically ethanolamine, the new non-ionic surfactant is specifically a block polyether, the environmentally friendly anionic surfactant is specifically sodium lignin sulfonate, the high-performance polyether is specifically polyethylene glycol ether, and the nano borate is specifically nano calcium borate.

[0027] The preparation method of the modified organic borate is specifically as follows: Step A1, first modification; Prepare boric acid, polyol and catalyst, weigh the raw materials boric acid and polyol, the molar ratio of boric acid: polyol is 1:1.2, the polyol is specifically ethylene glycol, the catalyst is specifically toluenesulfonic acid, and the dosage of the catalyst added is 0.5% of the total mass of the reactants; Add boric acid and polyol into a reaction kettle equipped with a stirring device, a thermometer and a reflux condenser, add a catalyst, slowly raise the temperature to 120°C, and keep stirring at this temperature for 3 hours; detect the acid value of the reaction system during the reaction, and stop the reaction when the acid value reaches a predetermined value; The predetermined value is an acid value less than 10 mgKOH / g; The reaction product is subjected to reduced pressure distillation to remove unreacted polyol and generated water to obtain a preliminarily modified boric acid ester; Step A2, second modification; Take the borate product obtained by the first modification, prepare an organic amine with anti-rust function and an initiator, the molar ratio of borate:organic amine is 1:1, the amount of initiator is 1% of the mass of the organic amine, the organic amine is specifically diethanolamine, and the initiator is specifically dibenzoyl peroxide; Add the borate product and organic amine to the reactor and stir evenly. Pass nitrogen to remove oxygen from the system. Heat to 80°C and add initiator. Maintain the temperature for 4 hours. After the reaction is completed, cool to room temperature. Step A3, third modification; Taking the second modified product, preparing a long-chain fatty acid and a catalyst with steric hindrance effect and environmental protection characteristics, the molar ratio of the second modified product: the long-chain fatty acid is 1:0.8, the amount of the catalyst is 0.5% of the mass of the long-chain fatty acid, the long-chain fatty acid is specifically stearic acid, and the catalyst is specifically tetrabutyl titanate; Add the second modified product and long-chain fatty acid into the reactor. Add the catalyst and stir evenly. Heat to 100°C and react for 3 hours to obtain the third modified organic borate. Step A4, modification and adjustment; Take the three modified organic borate products, prepare glycerophosphate and potassium carbonate, the amount of potassium carbonate is 2% of the mass of glycerophosphate; The final modified organic borate and glycerophosphate are added to a reactor equipped with a stirring device, a thermometer and a reflux condenser in a certain molar ratio of 1:0.5, and potassium carbonate is added. Under a nitrogen atmosphere, the temperature is slowly raised to 60°C and maintained at this temperature for 5 hours to obtain the final product, the modified organic borate.

[0028] The anti-rust function of glycerol phosphate is introduced into the organic borate system, thereby further enhancing its anti-rust performance; at the same time, the reaction conditions are relatively mild, which can reduce the damage to the original organic borate structure to a certain extent.

[0029] A production process of an environmentally friendly micro-emulsified cutting fluid comprises the following steps: Step B1, premixing; Add the base oil into the reactor, turn on the stirring device, control the stirring speed of the stirring device at 300r / min, and slowly raise the temperature to 40°C; add zinc dialkyl dithiophosphate, benzotriazole, organic alcohol amine, and Span in sequence during the stirring process, and stir for 15 minutes to obtain preliminary reagent A, so that these components are fully dissolved and evenly mixed in the base oil; Step B2, surfactant mixing; Add the new nonionic surfactant, environmentally friendly anionic surfactant and high-performance polyether to the preliminary reagent A, increase the stirring speed to 600r / min, and stir for 20 minutes to obtain the preliminary emulsified reagent B, so that the surfactant is fully mixed and interacts with the base oil and other ingredients to form a preliminary emulsified system. Step B3, nano borate dispersion treatment; Add nanoborate to deionized water and use an ultrasonic disperser to disperse the nanoborate for 20 minutes to evenly disperse the nanoborate in the water to form a nano suspension. Add the dispersed nanoborate suspension and preliminary emulsifying agent B into the reactor and stir at a stirring speed of 600 r / min for 15 minutes to obtain emulsion C; ensure that the nanoborate is evenly dispersed in the entire system. Step B4, adding water for emulsification; Slowly add deionized water to the reactor, control the water addition speed by flow meter, control the water addition speed at 1L per minute, maintain the stirring speed at 800r / min, and reduce the temperature of the reactor to 30℃; With the addition of water, the system gradually changes from an oil-in-water emulsion to an oil-in-water emulsion. Observe the state of the emulsion. When the emulsion becomes uniform, delicate and has no obvious oil droplets, it means that the emulsification is basically completed.

[0030] Step B5, adding modified organic borate and defoamer; Add the modified organic borate to the emulsion, reduce the stirring speed to 300r / min, and stir for 10 minutes to evenly disperse the modified organic borate in the cutting fluid to give full play to its anti-rust performance. Add an environmentally friendly defoaming agent and continue stirring for 5 minutes to finally obtain an environmentally friendly micro-emulsified cutting fluid.

[0031] The second embodiment is based on the first embodiment. An environmentally friendly micro-emulsified cutting fluid is composed of the following raw materials in parts by weight: 15 parts by mass of base oil, 3 parts by mass of zinc dialkyl dithiophosphate, 0.6 parts by mass of benzotriazole, 0.6 parts by mass of environmentally friendly defoaming agent, 9 parts by mass of organic alcohol amine, 12 parts by mass of new non-ionic surfactant, 1.5 parts by mass of environmentally friendly anionic surfactant, 8 parts by mass of high-performance polyether, 6 parts by mass of Span, 16 parts by mass of deionized water, 0.3 parts by mass of nano borate and 1.2 parts by mass of modified organic borate.

[0032] The environmentally friendly defoaming agent is specifically a natural oil defoaming agent, the organic alcohol amine is specifically ethanolamine, the new non-ionic surfactant is specifically a block polyether, the environmentally friendly anionic surfactant is specifically sodium lignin sulfonate, the high-performance polyether is specifically polyethylene glycol ether, and the nano borate is specifically nano calcium borate.

[0033] The preparation method of the modified organic borate is specifically as follows: Step A1, first modification; Prepare boric acid, polyol and catalyst, weigh the raw materials boric acid and polyol, the molar ratio of boric acid: polyol is 1:1.5, the polyol is specifically ethylene glycol, the catalyst is specifically toluenesulfonic acid, and the dosage of the added catalyst is 1% of the total mass of the reactants; Add boric acid and polyol into a reaction kettle equipped with a stirring device, a thermometer and a reflux condenser, add a catalyst, slowly raise the temperature to 150°C, and keep stirring at this temperature for 5 hours; detect the acid value of the reaction system during the reaction, and stop the reaction when the acid value reaches a predetermined value; The predetermined value is an acid value less than 10 mgKOH / g; The reaction product is subjected to reduced pressure distillation to remove unreacted polyol and generated water to obtain a preliminarily modified boric acid ester; Step A2, second modification; Take the borate product obtained by the first modification, prepare an organic amine with anti-rust function and an initiator, the molar ratio of borate:organic amine is 1.2, the amount of initiator is 3% of the mass of the organic amine, the organic amine is specifically diethanolamine, and the initiator is specifically dibenzoyl peroxide; Add the borate product and the organic amine to the reactor and stir evenly. Pass nitrogen to protect and remove oxygen from the system. Heat to 100°C and add initiator. Maintain the temperature for 6 hours. After the reaction is completed, cool to room temperature; Step A3, third modification; Taking the second modified product, preparing a long-chain fatty acid and a catalyst with steric hindrance effect and environmental protection characteristics, the molar ratio of the second modified product: the long-chain fatty acid is 1:1, the amount of the catalyst is 1% of the mass of the long-chain fatty acid, the long-chain fatty acid is specifically stearic acid, and the catalyst is specifically tetrabutyl titanate; Add the second modified product and long-chain fatty acid into the reactor. Add the catalyst and stir evenly. Heat to 120°C and react for 5 hours to obtain the third modified organic borate. Step A4, modification and adjustment; Take the three modified organic borate products, prepare glycerophosphate and potassium carbonate, the amount of potassium carbonate is -5% of the mass of glycerophosphate; The final modified organic borate and glycerophosphate are added to a reactor equipped with a stirring device, a thermometer and a reflux condenser in a certain molar ratio of 1:0.8, and potassium carbonate is added. Under a nitrogen atmosphere, the temperature is slowly raised to 80°C, and the reaction is maintained at this temperature for 8 hours with stirring to obtain the final product, the modified organic borate.

[0034] The anti-rust function of glycerol phosphate is introduced into the organic borate system, thereby further enhancing its anti-rust performance; at the same time, the reaction conditions are relatively mild, which can reduce the damage to the original organic borate structure to a certain extent.

[0035] The third embodiment is based on the first and second embodiments. An environmentally friendly micro-emulsified cutting fluid is composed of the following raw materials in parts by weight: 12.5 parts by mass of base oil, 2 parts by mass of zinc dialkyl dithiophosphate, 0.36 parts by mass of benzotriazole, 0.5 parts by mass of environmentally friendly defoaming agent, 8 parts by mass of organic alcohol amine, 10 parts by mass of new non-ionic surfactant, 1.2 parts by mass of environmentally friendly anionic surfactant, 7 parts by mass of high-performance polyether, 5 parts by mass of Span, 15 parts by mass of deionized water, 0.25 parts by mass of nano borate and 1 part by mass of modified organic borate.

[0036] The environmentally friendly defoaming agent is specifically a natural oil defoaming agent, the organic alcohol amine is specifically ethanolamine, the new non-ionic surfactant is specifically a block polyether, the environmentally friendly anionic surfactant is specifically sodium lignin sulfonate, the high-performance polyether is specifically polyethylene glycol ether, and the nano borate is specifically nano calcium borate.

[0037] The preparation method of the modified organic borate is specifically as follows: Step A1, first modification; Prepare boric acid, polyol and catalyst, weigh the raw materials boric acid and polyol, the molar ratio of boric acid: polyol is 1:1.3, the polyol is specifically ethylene glycol, the catalyst is specifically toluenesulfonic acid, and the dosage of the added catalyst is 0.6% of the total mass of the reactants; Add boric acid and polyol into a reaction kettle equipped with a stirring device, a thermometer and a reflux condenser, add a catalyst, slowly raise the temperature to 150°C, and keep stirring at this temperature for 4 hours; detect the acid value of the reaction system during the reaction, and stop the reaction when the acid value reaches a predetermined value; The predetermined value is an acid value less than 10 mgKOH / g; The reaction product is subjected to reduced pressure distillation to remove unreacted polyol and generated water to obtain a preliminarily modified boric acid ester; Step A2, second modification; Take the borate product obtained by the first modification, prepare an organic amine with anti-rust function and an initiator, the molar ratio of borate:organic amine is 1:1.15, the amount of initiator is 2% of the mass of the organic amine, the organic amine is specifically diethanolamine, and the initiator is specifically dibenzoyl peroxide; Add the borate product and organic amine to the reactor and stir evenly. Pass nitrogen to remove oxygen from the system. Heat to 95°C and add initiator. Maintain the temperature for 4 hours. After the reaction is completed, cool to room temperature. Step A3, third modification; Taking the second modified product, preparing a long-chain fatty acid and a catalyst with steric hindrance effect and environmental protection characteristics, the molar ratio of the second modified product: the long-chain fatty acid is 1:0.9, the amount of the catalyst is 1% of the mass of the long-chain fatty acid, the long-chain fatty acid is specifically stearic acid, and the catalyst is specifically tetrabutyl titanate; Add the second modified product and long-chain fatty acid into the reactor. Add the catalyst and stir evenly. Heat to 110°C and react for 4 hours to obtain the third modified organic borate. Step A4, modification and adjustment; Take the three modified organic borate products, prepare glycerophosphate and potassium carbonate, the amount of potassium carbonate is 2%-5% of the mass of glycerophosphate; The final modified organic borate and glycerophosphate were added into a reactor equipped with a stirring device, a thermometer and a reflux condenser in a certain molar ratio of 1:0.6, and potassium carbonate was added. Under a nitrogen atmosphere, the temperature was slowly raised to 70°C and kept stirring at this temperature for 7.5 hours to obtain the final product, the modified organic borate.

[0038] The anti-rust function of glycerol phosphate is introduced into the organic borate system, thereby further enhancing its anti-rust performance; at the same time, the reaction conditions are relatively mild, which can reduce the damage to the original organic borate structure to a certain extent.

[0039] Comparative Example 1, based on Examples 1, 2 and 3, An environmentally friendly micro-emulsified cutting fluid is composed of the following raw materials in parts by weight: 12.5 parts by mass of base oil, 2 parts by mass of zinc dialkyl dithiophosphate, 0.36 parts by mass of benzotriazole, 0.5 parts by mass of environmentally friendly defoaming agent, 8 parts by mass of organic alcohol amine, 10 parts by mass of new non-ionic surfactant, 1.2 parts by mass of environmentally friendly anionic surfactant, 7 parts by mass of high-performance polyether, 5 parts by mass of Span, 15 parts by mass of deionized water, 0.25 parts by mass of nano borate and 1 part by mass of borate ester.

[0040] The environmentally friendly defoaming agent is specifically a natural oil defoaming agent, the organic alcohol amine is specifically ethanolamine, the new non-ionic surfactant is specifically a block polyether, the environmentally friendly anionic surfactant is specifically sodium lignin sulfonate, the high-performance polyether is specifically polyethylene glycol ether, and the nano borate is specifically nano calcium borate.

[0041] Performance Testing pH value detection; Test method: Use a precision pH meter, insert the electrode into a cutting fluid sample that is fully mixed and has a stable temperature of about 25°C, and record the value after the pH meter reading stabilizes; Anti-rust performance testing; Test method: Use the wet heat chamber anti-rust test method. Soak the polished metal test pieces in the cutting fluid for 5 minutes, then take them out and hang them in a wet heat chamber with a temperature of 49°C and a relative humidity of 95%, and observe the time and degree of rusting of the test pieces; Anti-wear performance testing; Test method: Use a four-ball wear tester to test. Immerse the steel ball in the cutting fluid sample, and perform the wear test at a speed of 1200r / min, a load of 392N, and a time of 30 minutes. Measure the wear spot diameter of the steel ball after the test.

[0042] in conclusion: In terms of pH value, the cutting fluids of Examples 1, 2 and Comparative Example 1 are weakly alkaline, and the pH value range is conducive to providing certain rust prevention and corrosion inhibition effects during metal processing, and the numerical difference is affected by the raw material ratio. The pH value of Example 3 is relatively low, and the performance of Example 3 in this regard is relatively strong.

[0043] In terms of anti-rust performance, Examples 2 and 3 perform relatively well and can provide long-term anti-rust protection for the metal test piece. Example 1 is better than Comparative Example 1, which is significantly worse. This shows that the system of modified organic borate esters after multi-step modification and combined with other anti-rust components has significant advantages in rust prevention, and unmodified borate esters are difficult to achieve good anti-rust effects.

[0044] Among the anti-wear properties, Example 2 has the best anti-wear performance, and Examples 1 and 3 can also reduce the wear of the steel ball to a certain extent. The anti-wear ability of Comparative Example 1 is the weakest, indicating that the synergistic effect of modified organic borates and nano borates and other components can effectively reduce friction and wear, and the unmodified borates have limited effect in anti-wear.

[0045] In terms of harmful substance detection, Examples 1, 2, 3 and Comparative Example 1 all meet environmental protection standards, and no common harmful substances are detected, which reflects the reliability of the cutting fluid formula in terms of environmental protection and can meet the needs of processing scenarios with high environmental protection requirements.

[0046] In general, Example 3 is relatively outstanding in comprehensive performance, and the modified organic borate plays a vital role in improving the key properties of the cutting fluid such as rust resistance and wear resistance. Compared with the unmodified borate, it can significantly improve the overall performance of the cutting fluid.

[0047] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.

Claims

1. An environmentally friendly microemulsified cutting fluid, characterized in that: It is composed of the following raw materials in parts by weight: 10-15 parts by mass of base oil, 1-3 parts by mass of zinc dialkyl dithiophosphate, 0.3-0.6 parts by mass of benzotriazole, 0.3-0.6 parts by mass of environmentally friendly defoaming agent, 7-9 parts by mass of organic alcohol amine, 9-12 parts by mass of new non-ionic surfactant, 1-1.5 parts by mass of environmentally friendly anionic surfactant, 6-8 parts by mass of high-performance polyether, 4-6 parts by mass of Span, 14-16 parts by mass of deionized water, 0.15-0.3 parts by mass of nano borate and 0.6-1.2 parts by mass of modified organic borate.

2. The environmentally friendly microemulsified cutting fluid according to claim 1, characterized in that: It is composed of the following raw materials in parts by weight: 12.5 parts by mass of base oil, 2 parts by mass of zinc dialkyl dithiophosphate, 0.36 parts by mass of benzotriazole, 0.5 parts by mass of environmentally friendly defoaming agent, 8 parts by mass of organic alcohol amine, 10 parts by mass of new non-ionic surfactant, 1.2 parts by mass of environmentally friendly anionic surfactant, 7 parts by mass of high-performance polyether, 5 parts by mass of Span, 15 parts by mass of deionized water, 0.25 parts by mass of nano borate and 1 part by mass of modified organic borate.

3. The environmentally friendly microemulsified cutting fluid according to claim 2, characterized in that: The organic alcohol amine is specifically ethanolamine, the novel nonionic surfactant is specifically block polyether, the environmentally friendly anionic surfactant is specifically sodium lignin sulfonate, the high-performance polyether is specifically polyethylene glycol ether, and the nano borate is specifically nano calcium borate.

4. The environmentally friendly microemulsified cutting fluid according to claim 3, characterized in that: The preparation method of the modified organic borate is specifically as follows: Step A1, first modification; prepare boric acid, polyol and catalyst, weigh the raw boric acid and polyol; add boric acid and polyol into a reaction kettle, add catalyst, slowly heat to 120-150° C., and keep stirring at this temperature for 3-5 hours; detect the acid value of the reaction system during the reaction, and stop the reaction when the acid value reaches a predetermined value; perform vacuum distillation on the reaction product to obtain a preliminarily modified boric ester; Step A2, second modification; take the borate product obtained by the first modification, prepare an organic amine and an initiator; add the borate product and the organic amine into a reactor, stir evenly, and introduce nitrogen protection; heat to 80-100° C., add the initiator, maintain the temperature for 4-6 hours, and after the reaction is completed, cool to room temperature; Step A3, third modification; take the second modified product, prepare long-chain fatty acids and catalysts; add the second modified product and long-chain fatty acids into a reactor, add the catalyst, stir evenly, heat to 100-120° C., react for 3-5 hours, and obtain a tertiary modified organic borate; Step A4, modification and adjustment; take the above three modified organic borate products, prepare glycerophosphate and potassium carbonate, the amount of potassium carbonate is 2%-5% of the mass of glycerophosphate; the final modified organic borate and glycerophosphate are added to the reactor in a certain molar ratio of 1:0.5-0.8, potassium carbonate is added, and the temperature is slowly raised to 60-80°C under a nitrogen atmosphere, and the reaction is stirred at this temperature for 5-8 hours to obtain the final product modified organic borate.

5. The environmentally friendly micro-emulsified cutting fluid according to claim 4, characterized in that: In the step A1, the molar ratio of the raw material boric acid:polyol is weighed to be 1:1.2-1.5, the polyol is specifically ethylene glycol, the catalyst is specifically toluenesulfonic acid, and the dosage of the added catalyst is 0.5-1% of the total mass of the reactants; In step A2, the molar ratio of borate ester to organic amine is 1:1-1.2, the amount of initiator used is 1%-3% of the mass of the organic amine, the organic amine is specifically diethanolamine, and the initiator is specifically dibenzoyl peroxide; In the step A3, the molar ratio of the second modified product to the long-chain fatty acid is 1:0.8-1, the amount of the catalyst is 0.5%-1% of the mass of the long-chain fatty acid, the long-chain fatty acid is specifically stearic acid, and the catalyst is specifically tetrabutyl titanate.

6. A production process of an environmentally friendly micro-emulsified cutting fluid, characterized in that: The following steps are involved: Step B1, premixing; Add the base oil into the reactor and turn on the stirring device; During the stirring process, zinc dialkyl dithiophosphate, benzotriazole, organic alcohol amine and Span are added in sequence, and the stirring time is 15-20 minutes to obtain a preliminary reagent A; Step B2, surfactant mixing; Add a new nonionic surfactant, an environmentally friendly anionic surfactant and a high-performance polyether to the preliminary reagent A, increase the stirring speed to 600-800r / min, and stir for 20-30 minutes to obtain a preliminary emulsified reagent B; Step B3, nanoborate dispersion treatment; adding nanoborate to deionized water, using an ultrasonic disperser for dispersion treatment, the dispersion time is 20-30 minutes, to form a nano suspension; adding the dispersed nanoborate suspension and the preliminary emulsifying agent B to a reactor and stirring to obtain an emulsion C; Step B4, adding water for emulsification; slowly adding deionized water to the reactor, controlling the water adding speed by a flow meter, controlling the water adding speed at 1-2L per minute, maintaining the stirring speed at 800-1000r / min, and lowering the temperature of the reactor to 30-40°C; Step B5, adding modified organic borate and defoamer; adding the modified organic borate to the emulsion, reducing the stirring speed to 300-500r / min, stirring for 10-15 minutes, adding an environmentally friendly defoamer, and continuing stirring for 5-10 minutes to finally obtain an environmentally friendly micro-emulsified cutting fluid.

7. The production process of an environmentally friendly micro-emulsified cutting fluid according to claim 6, characterized in that: The stirring speed of the stirring device in step B1 is controlled at 300-500 r / min, and the temperature is slowly raised to 40-50° C.

8. The production process of an environmentally friendly micro-emulsified cutting fluid according to claim 6, characterized in that: In step B3, the stirring speed of the reactor is 600-800 r / min, and the stirring time is 15-20 minutes.